High-fidelity prediction of crack formation in 2D and 3D pullout tests. (August 2016) - Benedetti, Lorenzo; Cervera, Miguel; Chiumenti, Michele
Highlights: 2D and 3D pullout experimental tests on concrete specimens are modeled with Mixed FEM. An elasto-plastic model with a Rankine-based yield criterion is used for concrete. Mixed FEM provides enhanced convergence and stress accuracy in localization problems. Crack bifurcations, stress peaks, post peak behavior are predicted with high-fidelity. Abstract: This paper presents the 2D and 3D numerical analysis of pullout tests on steel anchorages in concrete blocks using standard and mixed finite elements. A novel (stabilized) mixed formulation in the variables of total strain ε and displacements u is introduced to overcome the intrinsic deficiencies of the standard displacement-based one in the context of localization of strains, such as mesh dependency. The quasi-brittle behavior of concrete is described through an elastoplastic constitutive law with a local Rankine yielding criterion. The proposed formulation is shown to be a reliable and accurate tool, sensitive to the physical parameters of the pullout tests, but objective with respect to the adopted FE mesh. Furthermore, the mixed ε / u finite element is able to capture the correct failure mechanism with relatively coarse discretizations. At the same time, the spurious behavior of the standard formulation is not alleviated by mesh-refinement.